MEMBUMIKAN ILMU WARIS SEBAGAI SOLUSI KONFLIK ANTAR SAUDARA AKIBAT PEREBUTAN HARTA WARIS - Muhammad Basirrudin; Isfandayani Isfandayani; Ria Mariginingsih (Universitas Islam 45 Bekasi, 2022)
Inheritance is property left by someone who has died, then the property is distributed to those who are entitled to receive it. In Islam, provisions regarding inheritance have been regulated, then it becomes a branch of science called inheritance science which contains discussions related to the provisions regarding inheritance. These provisions are regulated in order to create justice and benefit, not the other way around, namely conflicts and divisions between heirs. However, in reality, there are still many conflicts and divisions in society due to the distribution of inheritance. The activities carried out in this program are inheritance training which was attended by 23 youths from youth organizations in the North Bekasi area. The implementation of the program activity